2005
DOI: 10.1016/j.bbrc.2005.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Selective upregulation of immune regulatory and effector cytokine synthesis by intestinal intraepithelial lymphocytes following CD43 costimulation

Abstract: The involvement of the CD43 molecule in the activation of mouse small intestinal intraepithelial lymphocytes (IELs) has been studied using a panel of twenty-two regulatory and effector immune response analytes. In the absence of stimulation in vitro, IELs produced low levels of CCL5 only. Upon CD3 stimulation, the activity of seven of twenty-two analytes were elevated relative to unstimulated cultures, including several proinflammatory cytokines and chemokines. Notably, CD3 stimulation in the presence of CD43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…As previously described for anergic cells (35), when the first activating signals were provided by the TCR, we found that cells secreted primarily IL-8. Overall, our data support reports showing that CD43 functions as a coreceptor molecule for the TCR (15,36,37) and that CD43-mediated signals up-regulate the expression of several proinflammatory genes (27,38).…”
Section: Discussionsupporting
confidence: 79%
“…As previously described for anergic cells (35), when the first activating signals were provided by the TCR, we found that cells secreted primarily IL-8. Overall, our data support reports showing that CD43 functions as a coreceptor molecule for the TCR (15,36,37) and that CD43-mediated signals up-regulate the expression of several proinflammatory genes (27,38).…”
Section: Discussionsupporting
confidence: 79%
“…It remains to be determined how the presence or absence of CD43 on T cells is regulating Th cell differentiation. Studies in human T cells have shown that CD43 costimulation in the presence and absence of TCR stimulation can induce IFN-␥ production and promote Th1 differentiation (42)(43)(44)(45). However, these findings have not been replicated in murine systems, making it unclear whether this plays a role in our model.…”
Section: -Immunized Cd43contrasting
confidence: 46%
“…Costimulatory activity of CD43 leading to enhanced proliferation has been shown through in vitro studies involving anti‐CD43 cross‐linking in conjunction with TCR–CD3 stimulation (48). More importantly, significant differences have been shown with regard to cytokine profiles elicited following CD43 costimulation compared with CD3 stimulation alone or non‐stimulated cultures (49). Of 22 analytes tested, CCL5 was the only cytokine detected in non‐stimulated cultures (49).…”
Section: Constitutively Expressed Costimulatory Moleculesmentioning
confidence: 99%